Cryptosporidium varanii infection in leopard geckos (Eublepharis macularius) in Argentina - Dellarupe, Andrea (2016)
Cryptosporidiosis is observed in reptiles with high morbidity and considerable mortality. The objective of this study was to achieve the molecular identification of Cryptosporidium spp. in pet leopard geckos (Eublepharis macularius) from a breeder colony in Buenos Aires, Argentina. Oocysts comparable to those of Cryptosporidium spp. were detected in three geckos with a history of diarrhea, anorexia and cachexia. Molecular identification methods confirmed the presence of Cryptosporidium varanii (syn. C. saurophilum). This agent was considered to be the primary cause of the observed clinical disease. This is the first description of C. varanii infection in pet reptiles in Argentina.